Strength and power training in rehabilitation: Underpinning principles and practical strategies to return athletes to high performance - Maestroni, L.; Read, P.; Bishop, C.; Turner, A. (Sports Medicine, 2020)
Injuries have a detrimental impact on team and individual athletic performance. Deficits in maximal strength, rate of force development (RFD), and reactive strength are commonly reported following several musculoskeletal injuries. This article first examines the available literature to identify common deficits in fundamental physical qualities following injury, specifically strength, rate of force development and reactive strength. Secondly, evidence-based strategies to target a resolution of these residual deficits will be discussed to reduce the risk of future injury. Examples to enhance practical application and training programmes have also been provided to show how these can be addressed.